Pemograman Berbasis R untuk Analisis Vegetasi - Wiharto, Muhammad (bionature, 2009)
R is software as well as a functional programming language. This project use R to solve basic analysis of vegetation ecology. Vegetation parameters that computed with R are density, dominance, frequency, important value index, Shanon-Wenner’s diversity index. Various R function that use in order to derive result are attach ( ), data. frame ( ), apply ( ), is.na ( ), data.table ( ), detach ( ), rev ( ), sort ( ), tapply ( ), with ( ), and user defined function. Keywords: R software, functional programming, vegetation parameters, R function.